Fine-scale movements of the broadnose sevengill shark and its main prey, the gummy shark - Barnett, A; Abrantes, K; Stevens, JD; Bruce, BD; Semmens, JM (PLoS ONE, 2010)
Information on the fine-scale movement of predators and their prey is important to interpret foraging behaviours and activity patterns. An understanding of these behaviours will help determine predator-prey relationships and their effects on community dynamics. For instance understanding a predators movement behaviour may alter pre determined expectations of prey behaviour, as almost any aspect of the preys decisions from foraging to mating can be influencedby the risk of predation. Acoustic telemetry was used to study the fine-scale movement patterns of the Broadnose Sevengill shark Notorynchus cepedianus and its main prey, the Gummy shark Mustelus antarcticus, in a coastal bay of southeast Tasmania. Notorynchus cepedianus displayed distinct diel differences in activity patterns. During the day they stayed close to the substrate (sea floor) and were frequently inactive. At night, however, their swimming behaviour continually oscillated through the water column from the substrate to near surface. In contrast, M. antarcticus remained close to the substrate forthe entire diel cycle, and showed similar movement patterns for day and night. For both species, the possibility that movement is related to foraging behaviour is discussed. For M. antarcticus, movement may possibly be linked to a diet of predominantly slow benthic prey. On several occasions, N. cepedianus carried out a sequence of burst speed events(increased rates of movement) that could be related to chasing prey. All burst speed events during the day were across the substrate, while at night these occurred in the water column. Overall, diel differences in water column use, along with the presence of oscillatory behaviour and burst speed events suggest that N. cepedianus are nocturnal foragers, but may opportunistically attack prey they happen to encounter during the day.